PROVIDING FUNCTIONING AGRICULTURAL MARKET OF UKRAINE UNDER MARTIAL LAW CONDITIONS - BOIKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of the functioning of the agricultural market of Ukraine under martial law conditions. The theoretical and substantive characteristics of the agricultural market have been determined. It was established that the agricultural market should be understood as a specific sphere of exchange, within which the interests of producers and consumers of agricultural products are coordinated, taking into account the capacity of the market, its infrastructural capacities and the possibilities of solvent demand of the population. The expediency of adapting the parameters of the functioning of the agrarian market to the conditions of martial law is substantiated. The main problems of its development in the conditions of martial law have been identified, namely: rising prices for raw materials for the production of agricultural products, a decrease in the purchasing power of the population, an increase in the risk of food producers, blocking of sea ports for carrying out export-import operations, the destruction of the logistics infrastructure of the agricultural industry, the danger of conducting agricultural production in the de-occupied and front-line territories of Ukraine. A set of measures aimed at improving the functioning of the agricultural market of Ukraine in the conditions of martial law is proposed, including the provision of state support to food producers, the diversification of export and import channels in the agricultural sector, the development and restoration of the logistics capacities of the agricultural sector, the creation of logistics centers in the western border territories of Ukraine, improving the purchasing power of the most socially vulnerable sections of the population through targeted assistance tools, demining agricultural lands in the de-occupied territories and their reintegration into the process of agricultural production, improving the physical availability of food products for the population in the front-line zone, developing a network of wholesale trade facilities and developing agrarian and industrial clusters, facilitating access to the agricultural market of small producers of agricultural products on the basis of cooperation and integration.
Keywords: agricultural market; food; martial law conditions; logistics; risk; producers of agricultural products